The effectiveness of new revamp of Harian Metro at Klang Valley: Readers' perception and acceptance / Siti Hajar Mohd Salleh - Mohd Salleh, Siti Hajar (Faculty of Business and Management, 2006)
The purpose of this study is to identify the perception and acceptance level of HM's readers towards the new revamp at Klang Valley. It also will help the company to determine whether their new strategies had been done effectively or otherwise. Thus, the objectives of the study are to identify readers' perception, acceptance level and also reader's future intention towards new HM version. In line with the objectives, the factors to be studied to determine reader's perception and acceptance are the revamp criteria, customer buying behavior and demographic profile of the readers. In this study, researcher used secondary and primary data in collecting the necessary data. The sampling type used was the convenience sampling where 150 of respondents are being chosen to answer the questionnaires specifically at 4 selected areas; perception, acceptance level, buying intention and readers' profile after the new revamp of HM. The personal mall-intercept interview used to interview the respondents who were comprised of the current customers that had read HM. In order to run the data, Statistical Package for Social Science (SPSS) are been used. The finding also indicates that all 4 hypotheses are in the favor results. After the data collection, the result shows most of them are aware to the new revamp of HM. In fact, most of readers knew about the new revamp through television advertisement and all respondents assessed all elements on the new revamp as agree. From the finding, it is revealed that the profile of HM's readers is mostly female with range of age from 21-30 years old. The majority of the readers is Malays with the income less than RM1,000 and employed in private sectors. This potential market is mostly resident within Klang Valley. Hence, most readers obtain their copy of HM from convenience shop as they read it everyday. As for the features on customer buying behavior, readers affirmed as agree.